Analisis daya dukung air untuk pemenuhan kebutuhan air bersih pada Sistem Penyediaan Air Minum Regional Buleleng-Jembrana (SPAM Burana) - Komang Agus Aprianto; Putu Edi Yastika; I Nyoman Sudipa; I GD Yudha Partama (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Water carrying capacity is a crucial aspect in supporting sustainable regional development, particularly in ensuring the long-term preservation of water resources. Along with population growth, the demand for clean water in the Buleleng–Jembrana Regional Drinking Water Supply System (SPAM Burana), which serves the communities of Busungbiu, Seririt, Banjar, Gerokgak, and Melaya districts, has continued to increase. This increase is assessed through a comparison of water utilization, water availability, and water demand. The raw water source for SPAM Burana is the Titab–Ularan Dam, the largest dam on the island of Bali, with a storage capacity of up to 12 million cubic meters. This study adopts a quantitative approach, utilizing primary data collected directly from field surveys related to water availability and water demand, supported by secondary data such as rainfall and raw water supply. The objective of this research is to assess the status of water carrying capacity within the service area. The results indicate that Busungbiu Sub-district has a surplus water carrying capacity of 58,067,651.91 m³/year. Seririt Sub-district is projected to experience a water carrying capacity deficit over the next ten years, amounting to 111,962,158.70 m³/year. Banjar Sub-district shows a surplus water carrying capacity of 20,111,317.27 m³/year, while Gerokgak Sub-district faces a deficit of 3,557,397.91 m³/year. These findings suggest that although regional raw water availability is relatively sufficient, strategic regional development measures are required, including increasing household connection capacity, optimizing water distribution systems, and developing a comprehensive business plan for SPAM Burana to enhance the quality and sustainability of clean water services.